Systematic symptom screening in patients with advanced cancer treated in certified oncology centers: results of the prospective multicenter German KeSBa project - Braulke, Friederike; Para, Servet; Alt-Epping, Bernd; Tewes, Mitra; Bäumer, Markus; Haberland, Birgit; Mayer-Steinacker, Regine; Hopprich, Anne; de Wit, Maike; Grabe, Michaela; Bender-Säbelkampf, Sophia; Weßling, Caroline; et al. (Journal of Cancer Research and Clinical Oncology, 2023)
Purpose: Guidelines recommend a structured symptom screening (SC) for especially advanced cancer patients (CPs). The aim of this multicenter German prospective quality assurance project KeSBa (Kennzahl Symptom- und Belastungserfassung) was to gain knowledge on SC procedures in Oncology Centers (OCs) for advanced cancer patients and a first impression on the consequences of SC. Methods: The KeSBa project consisted of three phases: pilot, 3 months screening and feedback phase. Participating OCs decided to use either the Minimal Documentation System (MIDOS) or the Integrated Palliative care Outcome Scale (IPOS) and defined the cutoff values for positive screening results. Results: Out of 172 certified German OCs, 40 (23%) participated in the KeSBa pilot phase, 29 (16.8%) in the 3 months screening phase using MIDOS (n = 18, 58.6%) or IPOS (n = 11, 41.3%) and in the feedback round. 25/29 performed paper-based screening (86.2%). 2.963 CPs were screened. Results were documented for 1255 (42.2%, SC +) positive and 874 (29.5%, SC–) negative screenings depending on the center´s schedules: 452 SC + CPs (28.4%) and 42 SC– CPs (2.6%) had contact to specialized palliative care or other supportive specialist teams afterwards, 458 SC + CPs (28.8%) and 605 SC– CPs (38.1%) remained in standard oncology care. In the feedback round missing resources (personal and IT) and improved communication were mentioned most often. Conclusion: Routine SC is feasible in advanced CPs treated in OCs but associated with considerable workload. In 42.2% of CPs SC was classified as positive, indicating the need of further diagnostics or professional judgment. SC requires staff and IT resources.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Cancer; IPOS; MIDOS; Palliative; Screening; Supportive